PENYUSUNAN LAPORAN KEUANGAN BERBASIS TEKNOLOGI INFORMASI PAUD CITA SAKINAH - Novi Primita Sari; Muhammad Khoirul Fuddin (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
The success of the family as the first provider of educational assistance to children is very important, bearing in mind everything for the first time that is learned by children through family assistance. Today because of the times, many choose to work as a mother, so children are accepted to care for and are entrusted to relatives and others. Based on this phenomenon, there are many places where children gather with additional educational patterns that have a curriculum with various facilities and prices. One of them is the Cita Sakinah Child Care Park under the auspices of PDM Malang Regency. Exactly after the KH mosque. Ahmad Dahlan established for 4 years the management held a discussion with PCA and PCM and also members of the association made the decision to open a place for integrated early childhood education (PAUD) Cita Sakinah. The purpose of the establishment and opening of this PAUD is to make the symbols of honor from an early age, form the character of the child's independence and make the child behave and have principles based on Islam and Kemuhammadiyahan. Because it has only continued for 1 year PAUD in this system manages its finances is still very traditional by taking notes, so that through this community-based service program, assistance will be made in the preparation and preparation of integrated financial reports.